WARISAN PENJAJAHAN BELANDA DI INDONESIA PASCA-KOLONIAL (PERSPEKTIF PERUBAHAN DAN KESINAMBUNGAN) - Mestika Zed (Universitas Negeri Padang, 2017)
This paper is a preliminary exploration of the Netherlands colonial heritage in contemporary Indonesia (post-colonial). In this case there are three major issues that would like to set out one by one. First, about the degree of influence of colonization of the Netherlands in the Netherlands and Indonesia's relationship in the past. Second, about the impact of political and economic policies of the Netherlands colonial against the structure of the demographics of Indonesia. Third, an afterthought (reflection) about the importance of re-reading the historical experience of Netherlands colonial rule in the past and the legacy left behind, including the corpus of documents about the history of Indonesia and Netherlands’ relationship for research and learning history for the generation in the future. These three fundamental subjects will be viewed in the perspective of change and continuity. Finally, a cover blurb will spin back the important points set out in this paper.